(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
Among all the parchments used as cover material for notarial registers in the city of Piacenza, it stand out a bifolium containing a part of the most ancient communal statutes that dates back to the second half of 13th century. these unreleased statutes are meant to be added to the list of the already known ones. this paper aims to point out some aspects of the political context in which the statutes were edited. In this respect, it will be worth to take into account the clash between the milites and the Popolo of Piacenza, the fight against the Papacy and the Empire, and finally the lordship of Oberto Pelavicino, who controlled the city from 1253 to 1266. this paper will also provide a picture of the political support he received from the Popolo of Piacenza and the resulting relationship between them. DOI 10.17464/9788867742691